Spectrophotometric quantification of reactive oxygen, nitrogen and sulfur species in plant samples - Antoniou, Chrystalla; Savvides, Andreas M.; Georgiadou, Egli C.; Fotopoulos, Vasileios (My University, 2018)
Reactive oxygen, nitrogen and sulfur species are key signalling molecules involved in multiple physiological processes that can be examined in qualitative and quantitative manners. Here, we describe simple spectrophotometric assays that allow the quantification of hydrogen peroxide, nitrite-derived nitric oxide and hydrogen sulphide from plant tissues.
Keywords: Hydrogen peroxide; Hydrogen sulphide; Nitric oxide; Reactive species quantification; Spectrophotometry